Carbon Dioxide Enrichment PEBAX/MOF Composite Membrane for CO2 Separation - Po-Hsiang Tang (Membranes, 2021)
Zeolitic imidazole framework (ZIF-8) was incorporated into poly(ether-block-amide) (Pebax-1657) in differing ratios to prepare mixed matrix membranes (MMMs) for gas separation. As ZIF-8 loading is increased, gas separation selectivity also gradually increases. For economic considerations, the proportion of the increase in selectivity to the amount of MOF loaded per unit was calculated. The results show that mixing 5% MOF gives the best unit performance. With this, a variety of MOFs (UiO-66, UiO-66-NH2, A520, MIL-68(Al) and MIL-100(Fe)) were mixed with PEBAX at 5 loading to prepare MMMs. In this work, metal-organic frameworks (MOFs) were processed using the dry-free method, where in the synthesized MOF was not dried prior to incorporation. The gas separation performance test carried out shows the highest separation performance was exhibited by P-UiO-66, wherein the CO2/N2 gas selectivity was 85.94, and the permeability was 189.77 (Barrer), which was higher than Robeson’s Upper bound in 2008, and obtained a high permeability and selectivity among mixed matrix membranes. In the preparation of high quality MMMs for gas separation, details regarding the interface phenomenon were assessed.